Growth and development of bamboo in the coastal inundated area of Bangladesh - Miah, Md Abdul Quddus; Moula, Md Golam; Dey, AKM Azad and Tanmoy (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Bamboo has been introduced to coastal raised land under the Sonneratia apetala plantation and grew barren land in inundated areas in the western coastal belt of Bangladesh. This study aimed to quantify the bamboo growth in inundated areas at minimound, plain land, and barren land and under the S. apetala plantation and characterize the impact of inundation, soil pH, and soil salinity. The experimental plantation was carried out by B. vulgaris and B. balcooa on a mini-mound on barren coastal raised land in 2018. Other experiments of B. vulgaris were carried out on mini-mound and plain land under the S. apetala plantation in 2019 and 2020. Seedlings were raised by branch cutting. Mini mounds were prepared with soil. The soil sample was collected at different depths in off-peak and peak periods to determine soil pH, electrical conductivity (dsm-1), and nitrogen%. The growth of B. vulgaris in survival (p-value 0.0004) and new culms initiation% (p-value 0.0068) were significantly higher than B. balcooa in the barren land. Soil electrical conductivity showed significantly higher in all soil depths at barren land than under S. apetala forest in off-peak (p-value 0.0000, 0.0000, 0.0016) and peak periods (p-value 0.0002, 0.0028, 0.0000). The higher soil salinity affects the growth of two bamboo species. The higher soil pH affected the growth of B. balcooa on barren land. The growth performance of B. vulgaris showed significantly better survival% (p-value 0.030), height (p-value 0.0010), girth (p-value 0.011), total culms per clump (p-value 0.0086), and new culms initiation% (p-value 0.022) on the mini mound than plain land under S. apetala forest in 2019 and 2020 except height growth. The present study observed an inundation impact on the growth of B. vulgaris in the plain land plantation. B. vulgaris performed better on mini-mound under the S. apetala forest in inundated coastal areas. J. Asiat. Soc. Bangladesh, Sci. 49(1): 55-69, June 2023